PROFIL KEMAMPUAN MAHASISWA DALAM MENYELESAIKAN TUGAS MATA KULIAH PENGEMBANGAN PROGRAM PEMBELAJARAN BIOLOGI (P 3 B) DI PROGRAM STUDI BIOLOGI FKIP UNIVERSITAS RIAU PEKANBARU - Yustini Yusuf '; Raja Hussien Arief; Fitria Ruswinda Sari (Program Studi Pendidikan Biologi, 2014)
This study aims to determine the ability of the Student Profile Task CompletedCourse In Learning Program Development Biology (P3B) In Biology EducationProgram, University of Riau. This study was conducted in May 2012 to November2012 at the Faculty of Teacher Education Study Program of Biology, University ofRiau. This research is descriptive. The population of this study is the first semesterstudents and students of semester 2011/2012 2012/2013 using the total sample. Theparameters of this study consisted of primary data, lesson plans and worksheets onstudent class of 2010 and secondary data, lesson plans, worksheets, InstructionalMaterials, Media, and Assessment Tool for the student of 2009 Based on the resultsobtained for RPP research on student semester 2011/2012 (78.25%), student semester2012/2013 (70.09%), designing student worksheets on odd semester 2011/2012(74.82%), student semester 2012/2013 (60.06%), designing teaching materials (76 ,41%) medium (67.50%), and assessment tools (77.50%). It can be concluded that theability profile class of 2009 students who have taken classes in the first semester2011/2012 P3B in completing the task subjects P3B higher than regular student classof 2010 who have taken the course P3B in odd semester 2012-2013.Keywords: Profile, Development Biology Learning Program, Learning Tool